Draft Genome Sequence of Bacillus murimartini LMG 21005(T), an Alkalitolerant Bacterium Isolated from a Church Wall Mural in Germany - Wang, Jie-ping (Genome Announc, 2015)
Bacillus murimartini LMG 21005(T) is a Gram-positive, spore-forming, and alkalitolerant bacterium isolated from a church wall mural. Here, we report the 4.17-Mb genome sequence of B. murimartini LMG 21005(T), which will accelerate the application of this alkalitolerant bacterium and provide useful information for genomic taxonomy and phylogenomics of Bacillus-like bacteria.